KAJIAN PARTISIPASI PEREMPUAN TERHADAP KEGIATAN SIMPAN PINJAM PEREMPUAN (SPP) PNPM MANDIRI DI KOTA BENGKULU - Gita Mulyasari (University of Jember, 2015)
This research aims to determine how the level of female participation in SPP activities and analize the factors which related the level of female participation in PNPM Mandiri. The number of respondents in this research as many as 53 respondents. The method used ordinal scale to determine the level of participation of members of SPP and correlation Rank Spearman. The result in this research indicated that the level of participation of members of SPP activities is at the level of active participation and the factors related of level female participation are age, number of dependents, family income, and perception member about SPP activities in PNPM Mandiri. Keywords: female participation, SPP, PNPM Mandiri